Earthquakes triggered by the subsurface undrained response to reservoir impoundment at Irapé, Brazil - H. Raza; H. Raza; H. Raza; G. S. França; G. S. França; E. Sayão; V. Vilarrasa (Solid Earth)
The necessity to reduce carbon emissions to mitigate climate change is accelerating the transition from fossil fuels to renewable energy sources. Specifically, hydropower has emerged as a prominent and safe renewable energy source but entails reservoir-triggered seismicity (RTS). This phenomenon causes significant challenges for safe reservoir management. Irapé, in Brazil, is a prominent RTS site where seismicity surged after reservoir filling, with a maximum event of magnitude 3.0 in May 2006, just 6 months after the start of reservoir impoundment. Despite the fact that more than 1 decade has passed since the seismicity occurred, the factors governing these earthquakes and their connection to subsurface rock properties remain poorly understood. Here, we attempt to understand the potential causes of RTS at Irapé Dam, which is the highest dam in Brazil at 208 m and the second highest in South America. Permeability and porosity measurements of cylindrical cores from hard and intact rock samples, which were extracted near the RTS zone by pitting 10 cm from the surface, reveal a low-permeability rock. Porosity values range from 6.3 % to 14.7 %. Only 3 out of the 11 tested samples present permeability above the lowest measurable value of the apparatus (0.002 mD), with the highest permeability being 0.0098 mD. The undrained response of the low-permeability rock placed below the reservoir results in an instantaneous increase in pore pressure and poroelastic stress changes due to elastic compression, which brings potential faults located below the reservoir closer to failure conditions. According to our analytical calculations, the vertical loading caused by the increase of 136 m in the reservoir water level led to a 0.61 MPa pore pressure buildup in response to compression at the depth of the Mw 3.0 earthquake, i.e., 3.88 km, resulting in an increase of 0.75 MPa in the vertical effective stress and of 0.48 MPa in the horizontal effective stress. These changes resulted in an increase in the deviatoric stress that led to fault destabilization, causing the RTS. The laboratory measurements and analytical calculations corroborate the hypothesis that the initial seismic activity was induced by the undrained subsurface response to the reservoir loading at Irapé.